Natural infection of Lutzomyia longipalpis (Lutz & Neiva, 1912) by Leishmania infantum in a municipality with a high incidence of visceral leishmaniasis in the Brazilian Midwest - Herintha Coeto Neitzke-Abreu; Georgia Medeiros de Castro Andrade; Paulo Silva de Almeida; Gilmar Cipriano Ribeiro; Thaís Alves Ribeiro; D'Angela Maciel Barrios; Kamily Fagundes Pussi; José Dilermando Andrade Filho; Felipe Dutra-Rêgo; Fredy Galvis Ovallos (Sociedade Brasileira de Medicina Tropical (SBMT), 2023)
ABSTRACT Background: Here, Leishmania presence in sand flies from Três Lagoas, Mato Grosso do Sul, Brazil, after visceral leishmaniasis (VL) was investigated. Methods: In April 2022, two light traps were deployed within and around the residence for two days post-VL case report. Results: A total of 120 Lutzomyia longipalpis were collected. Suprapyloric flagellates were found in a female sand fly with eggs and residual blood during midgut dissection. Sequencing of ITS1 and cytb fragments confirmed Leishmania infantum DNA and identified Homo sapiens as the blood source, respectively. Conclusions: This study emphasizes the importance of monitoring sand flies in VL endemic areas.